Hall and ion slip effects on MHD free convective flow of chemical reaction - applications (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Hall and ion-slip impacts on unsteady MHD free convective laminar flow of an incompressible viscous, electrically conducting and heat generation/ absorbing fluid enclosed with a semi-infinite porous plate within a rotating frame has been premeditated. The plate is assumed to be moving with a constant velocity in the direction of fluid movement. A uniform transverse magnetic field is applied at right angles to the porous surface, which is absorbing the fluid with a suction velocity changing with time. The non-dimensional governing equations for present investigation are solved analytically making use of two term harmonic and non-harmonic functions. The graphical results of velocity, temperature and concentration distributions on the analytical solutions are displayed and discussed with reference to pertinent parameters. There is an intense world wide activity in the development of instrumentation for medical diagnosis and bio screening based on biological labeling and detection of nano particles. The skin friction coefficient increases in Hall and ion slip parameters. Out comes disclose that the impact of thermal convection of nano particles has increased the tempertature distribution, which helps in destroying the cancer cells during the drug delivery process.